The British election: A commentary - Panitch, Leo; Leys, Colin (Labour/Le Travail, 1997)
Critiques the British Labour Party's abandonment of its long-standing commitment to "parliamentary socialism" and the electoral platform of the incoming "New Labour" government of Tony Blair. Concludes that new forms of socialist organization are necessary since the path forward does not lie in transforming the Labour Party.